Gelatin-WS2 composite carbon material as well as preparation method and application thereof

The preparation of gelatin-WS2 composite carbon materials through lyophilization and carbonization processes solves the problems of high cost and insufficient capacitance performance of traditional carbon materials, and achieves electrochemical performance with high specific capacitance value, which is suitable for supercapacitor electrode materials.

CN119786273APending Publication Date: 2025-04-08CHANGZHOU UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411877496.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Traditional carbon materials are costly and polluted the environment, and the capacitance performance of gelatin as an electrode material needs to be improved.

Method used

Gelatin, sodium tungstate, thiourea and sodium chloride are used as raw materials to prepare honeycomb-like gelatin-WS2 composite carbon material with a honeycomb structure through lyophilization and carbonization processes, uniformly dispersing the tungsten and sulfur compounds to form a layered structure WS2.

Benefits of technology

The prepared gelatin-WS2 composite carbon material has good electrochemical properties, and the specific capacitance value reaches more than 200F/g. It is suitable for supercapacitor electrode materials, providing a new way of high performance, low cost and environmental protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention belongs to the technical field of carbon materials, and particularly relates to a gelatin-WS2 composite carbon material as well as a preparation method and application thereof. Biomass raw material gelatin is used as a carbon precursor and is mixed with sodium tungstate, thiourea and sodium chloride, freeze-drying and carbonization are performed to prepare a carbon material with a honeycomb structure, and the carbon material is applied to preparation of a supercapacitor electrode. The composite material has good electrochemical performance, and the specific capacitance value of the composite material reaches 200F / g or above (when the current density is 2A. G <-1 >) under the synergistic effect of uniformly dispersed tungsten disulfide, a hierarchical porous structure, a nitrogen-rich structure and other factors. And a new way is provided for developing a high-performance, low-cost and environment-friendly supercapacitor electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of carbon materials, and specifically relates to a gelatin-WS2 composite carbon material and a preparation method and application thereof. Background Art

[0002] It is crucial to convert sustainable energy into electrical energy using large-scale energy storage devices. As an energy storage technology, supercapacitors are high-capacity capacitors with excellent properties such as high power density, maintenance-free, and long life. Based on the unique structure and inherent storage mechanism of the device, three main types of supercapacitors can be identified: electric double layer capacitors (EDLCs), hybrid supercapacitors, and pseudocapacitors. With the continuous improvement of supercapacitors, the requirements for the storage capacity of their electrode materials will become higher and higher. Supercapacitors play a vital role in the field of energy storage with their long cycle stability, environmental friendliness, fast charging speed, and large power output.

[0003] Carbon materials have many excellent properties and are one of the effective methods to improve electrochemical performance. Biomass energy, as the most promising renewable energy, has become the fourth largest energy source in my country after coal, oil and natural gas. Biomass carbon materials have attracted widespread attention due to their simple production process, green and environmentally friendly, abundant sources and low prices.

[0004] Gelatin is a naturally derived biopolymer and a degradation product of the protein collagen. Its molecular chain is rich in amino acids and can be converted into N-doped carbon after carbonization. It has a rich pore structure and can provide a large specific surface area, which is conducive to the adsorption and diffusion of electrolyte ions. At the same time, it has low preparation cost and is sustainable, which is in line with the concept of modern green chemistry. However, as an electrode material, its capacitance performance needs to be further improved. Summary of the invention

[0005] In order to overcome the problems of high cost and environmental pollution of traditional carbon materials, the present invention provides a gelatin-WS2 composite carbon material and its preparation method and application, wherein gelatin, sodium tungstate, thiourea and sodium chloride are used as raw materials and freeze-dried and carbonized to obtain gelatin-WS2 carbon material. Specifically, the method comprises the following steps:

[0006] Step A: Mix gelatin and deionized water, stir and heat until the gelatin is completely dissolved to prepare a gelatin solution;

[0007] Step B: adding sodium tungstate, thiourea and sodium chloride to the gelatin solution prepared in step A, stirring until it is completely melted, and then freezing;

[0008] Step C: placing the sample obtained in step B into a freeze dryer for freeze drying, and placing the freeze dried sample into a tubular furnace for carbonization.

[0009] Furthermore, the usage ratio of gelatin and deionized water in step A is 0.5-1.0 g:30 ml.

[0010] Furthermore, the molar ratio of sodium tungstate to thiourea in step B is 1:5.

[0011] Furthermore, the amount of thiourea used in step B is 40% to 70% of the mass of gelatin.

[0012] Furthermore, the amount of sodium tungstate used in step B is 20% to 60% of the mass of gelatin, preferably 32.4 to 54.2%.

[0013] Furthermore, the freezing treatment temperature in step B is -80°C.

[0014] Furthermore, the inorganic salt in step B is a mixture of one or more of sodium chloride, potassium chloride, and calcium chloride, and the amount used is 60% to 80% of the total mass of sodium tungstate and thiourea.

[0015] Furthermore, the specific steps of the gradient carbonization process in step C are as follows:

[0016] The freeze-dried sample was placed in a tubular furnace filled with nitrogen, heated to 300°C at a heating rate of 3°C / min, then heated to 600-700°C at a heating rate of 5°C / min, kept at that temperature for 60-120 min, and taken out after cooling in the furnace.

[0017] Furthermore, the carbonized sample was washed with deionized water and then dried in a vacuum drying oven at 80° C. for 120 min.

[0018] Application of the gelatin-WS2 composite carbon material prepared above in the preparation of electrodes.

[0019] Furthermore, the specific steps of the electrode preparation method are as follows:

[0020] The obtained gelatin-WS2 composite carbon material, carbon black, and polytetrafluoroethylene were mixed in a mass ratio of 8:1:1, and anhydrous ethanol was added to form a uniform suspension. After ultrasonic dispersion for 30 minutes, the suspension was placed in an oven and dried for 1 to 2 hours until it became viscous. The suspension was then coated on an area of ​​1 cm 2 The electrode was obtained after being dried on the nickel foam.

[0021] Compared with the prior art, this application has the following technical advantages:

[0022] 1. The present invention uses gelatin as a precursor for producing nitrogen-doped carbon, and mixes it with sodium tungstate, thiourea and sodium chloride, and then freeze-dries and carbonizes it to prepare a composite carbon material with a honeycomb structure, wherein the tungsten compound and the sulfur compound are uniformly dispersed in the mixed material, and form a layered structure WS2 during the carbonization process, which is uniformly dispersed and embedded in the porous structure, and is assembled into a hierarchical porous structure by combining freeze-drying and carbonization of gelatin.

[0023] 2. The reaction conditions of the present invention are relatively mild, the operation is simple, there is no emission of other waste materials, it belongs to an environmentally friendly process route, pyrolytic carbon with pure components can be obtained, the reaction yield is high, and cost is saved.

[0024] 3. The gelatin-WS2 composite carbon material prepared by the present invention can be used as an electrode material for electrochemical applications. It has good electrochemical properties. Under the synergistic effect of uniformly dispersed tungsten disulfide, hierarchical porous structure, nitrogen-rich structure and other factors, its specific capacitance reaches more than 200F / g (current density is 2A·g -1 It provides a new way to develop high-performance, low-cost and environmentally friendly supercapacitor electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a comparison diagram of CV curves of electrode materials prepared from carbon materials obtained in Example 1 and Comparative Example 1 at the same scanning rate;

[0026] Figure 2 This is a comparison diagram of CV curves of electrode materials prepared from carbon materials obtained in Example 2 and Comparative Example 2 at the same scanning rate;

[0027] Figure 3 CV curve comparison diagram of the carbon material prepared in Example 1 at different scanning rates;

[0028] Figure 4 The constant current charge and discharge diagrams of the carbon material prepared in Example 1 at different current densities;

[0029] Figure 5 This is an EDS image of the carbon material prepared in Example 1;

[0030] Figure 6 This is a SEM image of the carbon material prepared in Example 1. DETAILED DESCRIPTION

[0031] The present invention is not limited to the following specific embodiments. A person skilled in the art can implement the present invention in various other specific embodiments according to the contents disclosed in the present invention, or any simple changes or modifications made to the design structure and ideas of the present invention fall within the protection scope of the present invention. It should be noted that the embodiments and features in the embodiments of the present invention can be combined with each other without conflict.

[0032] The method of the present invention is further described below in conjunction with embodiments, which are not intended to limit the present invention.

[0033] Example 1

[0034] Add 0.54g gelatin and 30mL deionized water to a 50ml beaker, heat to 50℃ to completely dissolve it, then add 0.293g sodium tungstate, 0.38g thiourea, and 0.45g sodium chloride and stir to mix evenly. The mass of ammonium tungstate is 54.2% of the mass of gelatin. Place the prepared sample in a -80℃ refrigerator for freezing treatment, and the freezing time is 12h. Place the treated sample in a freeze dryer for freeze drying. Place the obtained sample in a tubular furnace, heat it to 300℃ at a heating rate of 3℃ / min, change the heating rate to 5℃ / min, the carbonization temperature to 700℃, the carbonization time to 2h, cool it to room temperature, wash it with deionized water, and place it in a vacuum drying oven at 80℃ for 120min to obtain gelatin-WS2 composite carbon material.

[0035] The carbon material prepared in Example 1 was applied to the preparation of an electrode and an electrochemical test was performed. The specific steps are as follows:

[0036] (1) Take 0.73g of gelatin-WS2 composite carbon material, and then weigh it with acetylene black and polytetrafluoroethylene in a mass ratio of 8:1:1. After mixing the three, add 20mL of anhydrous ethanol to form a uniform suspension. After ultrasonic dispersion for 30min, take it out and put it in an oven for 1.5h. After the mixture is dried to a viscous state, take 0.0123g of the mixture and apply it on an area of ​​1cm 2 On the nickel foam, the electrode material was obtained after drying for 12 hours;

[0037] (2) Preparation of electrolyte: Prepare a 2M KOH solution;

[0038] (3) Electrochemical test: The working electrode is the electrode material prepared in step (1), the reference electrode is a calomel electrode, and the counter electrode is a platinum electrode. The electrodes are placed in an electrolyte and an electrochemical workstation is used to perform cyclic voltammetry test, constant current charge and discharge test, impedance test, and cycle life test: the cyclic voltammetry test scan speed is 0.1 v / s, 0.2 v / s, 0.3 v / s, 0.4 v / s, 0.5 v / s, the voltage range is -0.5 to 0.5 V, forward scan: the high potential is set to 0.5 V (relative to the reference electrode), the low potential is set to -0.5 V (relative to the reference electrode), reverse scan: the high potential is set to -0.5 V (relative to the reference electrode), the low potential is set to 0.5 V (relative to the reference electrode); the constant current charge and discharge test current density is 1 A g -1 , 2A·g -1 , 3A g -1 , 5A g -1 , the voltage range is -0.5~0.5V.

[0039] After testing, Figure 3 The cyclic voltammetry curves at different scan rates in the voltage range of -0.5 to 0.5 V show that as the scan rate increases, the curve area increases, and the curve is rectangular, showing good electrochemical performance. The redox reaction is basically reversible during the charge and discharge process, such as Figure 4 The constant current charge and discharge curves at different current densities are shown in Figure 2. When the current density is 1A·g -1 The specific capacitance value reaches 403F / g. When the current density is 2A·g -1 , its specific capacitance value reaches 290F / g.

[0040] Example 2

[0041] Based on Example 1, the carbonization temperature was changed to 600°C.

[0042] The electrochemical performance of the gelatin-WS2 composite carbon material prepared in Example 2 was measured by constant current charge and discharge test with a voltage range of -0.5 to 0.5 V. When the current density was 2 A·g -1 When , the specific capacitance value is 133F / g.

[0043] Example 3

[0044] On the basis of Example 1, the amount of gelatin added was changed to 0.90 g, and the mass of ammonium tungstate was 32.5% of the mass of gelatin.

[0045] The electrochemical performance of the gelatin-WS2 composite carbon material prepared in Example 3 was measured. The voltage range was -0.5 to 0.5 V. When the current density was 2 A·g -1 When the specific capacitance is 244F / g.

[0046] Example 4

[0047] Based on Example 3, the carbonization temperature was changed to 600°C.

[0048] The electrochemical performance of the gelatin-WS2 composite carbon material prepared in Example 4 was measured. The voltage range was -0.5 to 0.5 V. When the current density was 2 A·g -1 When the specific capacitance is 74F / g.

[0049] Comparative Example 1

[0050] Add 0.54g of gelatin and 30mL of deionized water to a 50ml beaker, heat to 50℃ to completely dissolve it, and place the prepared sample in a -80℃ refrigerator for freezing treatment for 12h. Place the treated sample in a freeze dryer for freeze drying. Place the obtained sample in a tubular furnace, heat it to 300℃ at a heating rate of 3℃ / min, change the heating rate to 5℃ / min, the carbonization temperature to 700℃, the carbonization time to 2h, and cool it to room temperature to obtain a gelatin-based carbon material.

[0051] The carbon spheres prepared in Comparative Example 1 were used to prepare electrodes and electrochemical tests were performed. The specific steps are as follows:

[0052] (1) Take the gelatin-based carbon material prepared in Comparative Example 1, and then weigh it with acetylene black and polytetrafluoroethylene in a mass ratio of 8:1:1. After mixing the three, add 20 mL of anhydrous ethanol to form a uniform suspension. After ultrasonic dispersion for 30 minutes, take it out and put it in an oven for 1.5 hours. After the mixed solution is dried to a viscous state, take 0.03 g of the mixture and apply it on nickel foam. After drying for 12 hours, the electrode material is obtained;

[0053] (2) Preparation of electrolyte: Prepare a 2M KOH solution;

[0054] (3) Electrochemical test: Same as Example 1.

[0055] The electrochemical performance was measured, the voltage range was -0.5~0.5V, when the current density was 1A·g -1 When the specific capacitance is 37F / g.

[0056] Comparative Example 2

[0057] Add 0.54g gelatin and 30mL deionized water to a 50ml beaker, heat to 50℃ to completely dissolve it, and place the prepared sample in a -80℃ refrigerator for freezing treatment for 12h. Place the treated sample in a freeze dryer for freeze drying. Place the obtained sample in a tubular furnace, heat it to 300℃ at a heating rate of 3℃ / min, then change the heating rate to 5℃ / min and the carbonization temperature to

[0058] 600℃, carbonization time is 2h, and cooling to room temperature obtains gelatin-based carbon material.

[0059] The carbon material prepared in Comparative Example 2 was applied to the preparation of an electrode and an electrochemical test was performed. The specific steps are as follows:

[0060] (1) Take the gelatin-based carbon material prepared in Comparative Example 1, and then weigh it with acetylene black and polytetrafluoroethylene in a mass ratio of 8:1:1. After mixing the three, add 20 mL of anhydrous ethanol to form a uniform suspension. After ultrasonic dispersion for 30 minutes, take it out and put it in an oven for 1.5 hours. After the mixed solution is dried to a viscous state, take 0.03 g of the mixture and apply it on nickel foam. After drying for 12 hours, the electrode material is obtained;

[0061] (2) Preparation of electrolyte: Prepare a 2M KOH solution;

[0062] (3) Electrochemical test: Same as Example 1.

[0063] The electrochemical performance was measured, the voltage range was -0.5~0.5V, when the current density was 1A·g -1 When the specific capacitance is 30F / g.

[0064] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical solutions and concepts of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing a gelatin-WS2 composite carbon material, characterized in that: The method comprises the following steps: using gelatin, sodium tungstate, thiourea and sodium chloride as raw materials, freezing, freeze-drying and carbonizing to obtain gelatin-WS2 carbon material.

2. The method for preparing the gelatin-WS2 composite carbon material according to claim 1, characterized in that: Specific steps: Step A, mixing gelatin and a solvent, stirring and heating until the gelatin is completely dissolved to prepare a gelatin solution; Step B, adding sodium tungstate, thiourea and sodium chloride to the gelatin solution prepared in step A and stirring until it is completely melted; Step C: freeze-drying the sample obtained in step B, and then carbonizing it.

3. The method for preparing the gelatin-WS2 composite carbon material according to claim 2, characterized in that: The molar ratio of sodium tungstate to thiourea is 1:

5.

4. The method for preparing the gelatin-WS2 composite carbon material according to claim 2, characterized in that: The dosage of the sodium tungstate is 20% to 60% of the mass of gelatin.

5. The method for preparing the gelatin-WS2 composite carbon material according to claim 2, characterized in that: The dosage of the thiourea is 40% to 70% of the mass of gelatin.

6. The method for preparing the gelatin-WS2 composite carbon material according to claim 2, characterized in that: The inorganic salt is a mixture of one or more of sodium chloride, potassium chloride and calcium chloride, and the dosage is 60% to 80% of the total mass of sodium tungstate and thiourea.

7. The method for preparing the gelatin-WS2 composite carbon material according to claim 2, characterized in that: The specific steps of the gradient carbonization process are as follows: The freeze-dried sample was placed in a tubular furnace with nitrogen, heated to 300°C at a rate of 3°C / min, then heated to 600-700°C at a rate of 5°C / min, kept at that temperature for 60-120 minutes, and then taken out after cooling in the furnace. After washing with deionized water, the sample was placed in a vacuum drying oven for drying.

8. A gelatin-WS2 composite carbon material prepared according to the method according to any one of claims 1 to 7.

9. A use of the gelatin-WS2 composite carbon material according to claim 8 in preparing an electrode, characterized in that: The gelatin-WS2 composite carbon material, carbon black and polytetrafluoroethylene are mixed, and anhydrous ethanol is added to form a uniform suspension. After ultrasonic dispersion, the mixture is placed in an oven to be dried until it becomes viscous, and then coated on the nickel foam and dried to obtain an electrode.

Citation Information

Patent Citations

  • Preparation method of non-water-soluble transition metal disulphide nanosheets

    CN105140517A

  • Molybdenum (tungsten) diselenide (disulfide) / carbon composite material as well as preparation method and application thereof

    CN106816602A